Source rock potential, thermal maturity, and depositional environment of the Ordovician Ra’an Shale Member, central Saudi Arabia - AlGhamdi, Faisal; Babalola, Lamidi; Alqubalee, Abdullah; Abu-Mahfouz, Israa S.; Alotaibi, Bandar; Abouelresh, Mohammed (Journal of Asian Earth Sciences: X, 2024)
•Three main lithofacies were identified in the Ordovician Ra’an Shale.•Elemental analysis indicates anoxic marine conditions during deposition.•Microscopic investigation reveals various pore systems.•Ra’an Shale exhibits kerogen types III and II/III, with a poor/fair HC potential.•Maturity parameters indicate mainly an immature source rock sequence.•Weathering index indicates high weathering rates, causing TOC reduction. The Ordovician Ra’an Shale Member of the Qassim Formation in Saudi Arabia has potential as an unconventional hydrocarbon play. This shale unit, however, has not been studied in detail for its geochemical characteristics, thermal maturity, and reservoir quality. This study aims to investigate this shale member from a well-exposed section at Khashm Ra’an in the Qassim region, central Saudi Arabia. Detailed fieldwork followed by comprehensive geochemical and petrographic analyses were conducted to evaluate the hydrocarbon potential and interpret the depositional setting of this shale member. Integration of field sedimentological description, sample description and thin section petrography facilitated the identification of partially burrowed laminated fish-bearing shale, bioturbated siltstone, graptolite-bearing shale, shale/siltstone and sandstone/shale interbeds in the investigated outcrop. The intervals were sandwiched between the bioturbated sandstone of the underlying Kahfah Sandstone and the overlying Quwarah Formation. These lithofacies are interpreted to have been deposited in a shallow marine depositional setting. The preservation of graptolite in some intervals indicates low bottom dissolved oxygen conditions. The mineralogical analysis indicated that clay minerals, quartz, and feldspars are the major mineralogical components in the study samples. Based on mineralogical compositions, the studied samples were classified into three main lithofacies types; silica-rich argillaceous mudstone, clay-rich siliceous mudstone, and mixed siliceous mudstone lithofacies. Elemental analysis proxies indicated that most of the tested samples were deposited in anoxic environment. The calculated values of the chemical index of weathering (CIW) indicated that samples were exposed to high rates of weathering, which negatively impacted organic matter preservation. Microscopic investigation identified the pore systems of the Ra’an Member as interparticle, interparticle and fracture pore systems, and observed the diagenetic features in the form of cementation, compaction, and dissolution. Organic geochemical analysis indicates that the samples are mainly of kerogen type III and II/III with poor to fair potential for hydrocarbon generation. This study provides an improved understanding of the depositional setting, organic geochemical, and thermal evolution of the Ra'an Member as a potential unconventional hydrocarbon reservoir.